STRATEGIC ADAPTATION OF A BUSINESS GROUP ORIGINATED IN A SAFETY MATCHES INDUSTRY - Sampaio, Gustavo Cristiano (2016)
The issue of environmental determinism and voluntarism has generated extensive discussion in the strategy area. This paper analyzes the process of strategic adaptation of a business group originated in a safety matches industry. A longitudinal case study was used, with data collection conducted through documentary analysis and semi-structured interviews, further an analysis via contextual and procedural approach proposed by Pettigrew (1987), and through the determinism and voluntarism model proposed by Hrebiniak and Joyce (1985). The results demonstrate that voluntarism prevailed on the adapting process of the company, sometimes accompanied by high environmental determinism.